2003
DOI: 10.1080/11250000309356522
|View full text |Cite
|
Sign up to set email alerts
|

The mandibular glands as a source of sexual pheromones in virgin queens ofPolyergus rufescens(Hymenoptera, Formicidae)

Abstract: 'Female-calling syndrome' is the reproductive strategy adopted by the European slave-making ant Polyergus rufescens, where a winged female disperses a short distance from the nest, ascends to an elevated position (at the top of a blade of grass) and is joined shortly thereafter by conspecific males. This suggests the probable use of very effective sexual calling pheromones by females. Here, the role of the mandibular glands of winged females is demonstrated to be a source of sexual pheromones. The secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…1 The basic absence in this gland secretion of substances other than 1 strongly supports the hypothesis that this compound is the sex pheromone used by females to call for males. The next step of our research will be a behavioral bioassay, which should clarify definitely the role of 1 in attracting P. rufescens males.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…1 The basic absence in this gland secretion of substances other than 1 strongly supports the hypothesis that this compound is the sex pheromone used by females to call for males. The next step of our research will be a behavioral bioassay, which should clarify definitely the role of 1 in attracting P. rufescens males.…”
supporting
confidence: 50%
“…5,7 Following this strategy, we have just published a report on the Dufour's gland content of workers of two ant species of the genus Messor, analyzed by SPME/GC/MS directly on the intact insect gland. 8 In a previous study, 1 we demonstrated the implication of mandibular glands of P. rufescens virgin queens in the attraction of males for mating. A similar result was reached in the American species P. breviceps.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…) and P. rufescens (Grasso et al . ); as an antimicrobial substance in Calomyrmex workers (Brough ); as an attraction pheromone for workers in queens of Myrmica rubra , M. rugulosa and M. schencki (Cammaerts ; Cammaerts et al . ); as a nestmate recognition pheromone in A. laevigata (Hernández et al .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, secretions from this gland are discharged in the air through a peculiar curved slit of the mandible cuticle and convey signals by which virgin females attract males for mating. Female calling by mandibular gland secretions is a rare phenomenon in ants, and in P. rufescens may be regarded as an adaptation to the parasitic life (Grasso et al 2003(Grasso et al , 2004.…”
Section: Introductionmentioning
confidence: 99%